No effect of low-dose aspirin for the prevention of heterotopic bone formation after total hip replacement: a randomized trial of 2,649 patients. - Neal, B; Rodgers, A; Gray, H; Clark, T; Beaumont, D; House, T; Douglas, J; Reid, I; MacMahon, S (2000)
2,649 patients scheduled for elective total hip replacement were recruited to the Heterotopic Bone Formation Sub-study of the Pulmonary Embolism Prevention Trial. Heterotopic bone formation was determined by radiographic examination and associated late postoperative outcomes were assessed by telephone interview. Heterotopic bone formation was observed in 627 (31%) of 2,048 radiographic examinations. There was no detectable effect of low-dose aspirin on the risks of heterotopic bone formation (RR 0.98; 95% CI 0.85-1.12), late postoperative pain (RR 1.10; 95%CI 0.91-1.35) or late postoperative impaired function (RR 1.03; 95% CI 0.94-1.12). The balance of benefits and risks of low-dose aspirin is determined by its effects on vascular events and bleeding, since it has no major effects on heterotopic bone formation or associated clinical outcomes.